Re-evaluating the effect of mergers and acquisitions on the short-run performance of the European banking institutions - Iasinskyi, Mykhailo (2017)
The last two decades since the early 1990s were characterised by important factors that influenced the banking institutions in the EU – introduction of the euro, globalisation, deregulation and technological advance. The speed and depth of these changes were unprecedented. For many European banks, mergers and acquisitions (M&A’s) became a universal response to these trends. Consequently, the number of operating banks has been continuously decreasing since the early 1990s due to integration processes. However, the influence of the above-mentioned factors was studied insufficiently in the existing literature, and the obtained results were mixed and inconclusive. The thesis attempts to add to the knowledge on M&A’s and to determine the impact of external shocks in relation to the banking acquisitions in the European Union. The thesis re-evaluates and investigates the role of the introduction of the euro in the post-merger outcomes in the European banking sector. Following the methodology by Ekkayokkaya et al., (2009), the analysis is replicating the paper based on the sample of 1479 banking mergers in 1990-2004 and is further extending the research to the period of 1990-2015 to capture the abnormal returns for the banks involved into M&A processes and to establish the influence of the global financial crisis on the shareholders’ wealth. As a useful improvement, the scope of the modern EU configuration was incorporated into second part of the analysis to reflect the economic, financial, social similarities between the EU states, as well as the integration efforts that were applied since the early 1990s. It was confirmed that the positive effect from the elimination of currency-related borders did not outweigh the negative effect of the intensified competition for the limited banking assets in the EU. Overall, the introduction of the euro was one of the factors that played a negative role for the short-run outcomes of the merging institutions. Further, a process of the short-run value creation in banking mergers among the European banks was studied for the period of 1990-2004 (replication of Asimakopoulos and Athanasoglou, 2013) and then extended to 1990-2015 in an attempt to capture the role of the global financial crisis. By utilising market-based approach (event study methodology), it was found that the global financial crisis was among the factors that caused a distinctive negative effect on the changes in the shareholders’ wealth of both acquirers and targets. On average, bidders experienced losses of -1.15% during the active phase of the crisis (2007-2009). Both focused and diversifying M&A’s were value-destroying; however, the only type of targets, that was able to bring positive gains to the bidders, was investment companies. It was also found that market was able to react positively on the deals announced during the crisis, thus showing optimistic attitude to the efforts to diversify into the other industries. Overall, banks were unable to benefit from low asset prices due to their own poor financial performance and economic uncertainty. The second perspective analysed in the thesis was the attempt to utilise the combined approach by deploying market-based methodology (event study) and the methodology based on the accounting data, following Asimakopoulos and Athanasoglou (2013). The objective was to replicate the above-mentioned study and determine the connection between short-run market reaction on the M&A’s and the accounting variables presented by financial ratios. Further, the research was extended to cover modern EU-28 configuration and time period between 1990 and 2015. As a result, 197 bank-to-bank acquisitions were analysed using market return model and subsequently by applying OLS- and GARCH-based regression analysis. The findings indicate that mergers do not create value for the bidders’ shareholders, whereas targets’ shareholders benefit from +2.5% growth in their wealth. It was also found, that accounting data provides a weak explanation of the abnormal returns around the deal announcement. Only bank size was considered to be negatively related to the cumulative abnormal returns, implying that integration costs are likely to be the key barrier towards the post-acquisition synergies. The findings also indicate the most value-generating mergers in the sample are deals between smaller banks with higher profitability and lower credit risks.